Predictors of in-Hospital Prognosis after Primary Percutaneous Coronary Intervention for Acute Myocardial Infarction Requiring Mechanical Support Devices - Nasir Ali, Rizwan Ullah, Saeed Maqsood, Tariq Ahmed, Shahzad Khatti, Rabnawaz Khan, Tahir Saghir (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: The study was designed to identify predictor variables of the hospitalized patient’s primary percutaneous coronary intervention (PPCI) for MI needing mechanical support systems including some intra-aortic balloon-pumping and percutaneous cardiopulmonary. However, these predictors are still unknown. Place and Duration: The research was carried out at National Institute of Cardiovascular Disease with the duration from 5th September 2021 to 5th March 2022. Methodology: Clinical history, angiographic research results, primary PCI outcomes, as well as in hospital prognosis were retroactively evaluated by comparing primary PCI treated acute myocardial infarction patients needing mechanical aid devices (with intra-aortic balloon pump patient populations, n=550) versus those without (IABP patients, n=755). In comparison to individuals without IABP, those with intra-aortic balloon pump were much more inclined to have a greater proportion of diseased vessels, a lower TIMI score in the infarct related artery (IRA), and a considerably high death rate of hospitalized patients. On multivariate analysis, possession of Thrombolysis In Myocardial Infarction greater than or equal to 3 flow in the infarct-related artery right after PPCI was the poor indicator in the without intra-aortic balloon pump patients, in contrast to the patients with IABP. The percentage of diseased vessels or diseased left main trunk at preliminary cardiac catheterization was the impartial predictive factor of the hospitalized patient’s fatalities in the sufferers with IABP, but not in the sufferers without intra-aortic balloon pump. Results: A significant risk factor for fatality in hospitalized patients in PPCI-treated acute myocardial infarction patients needing mechanical assistance devices is the proportion of diseased vessels ≥ 2 or diseased left main trunk at baseline CAG. Keywords: Percutaneous cardiopulmonary support; Intra-aortic balloon pumping, PPCI or primary percutaneous coronary intervention; Multi-vessel disease